The potential link between sugar-sweetened beverage consumption and post-exercise airway narrowing across puberty: a longitudinal cohort study - Emerson, Sam R.; Rosenkranz, Sara K.; Rosenkranz, Richard R.; Kurti, Stephanie P.; Harms, Craig A. (My University, 2015)
Objective The prevalence of asthma is rising, presenting serious public health challenges. Recent data suggest that sugar-sweetened beverage (SSB) consumption plays a role in asthma aetiology. The purpose of the present study was to determine whether SSB consumption is linked to post-exercise airway narrowing (predictor of asthma development) across puberty. Design Participants completed pulmonary function tests, physical activity and dietary habit questionnaires, and an exercise test to exhaustion. Setting Community in Manhattan, Kansas, USA. Subjects We recruited ten boys and ten girls from an original cohort of forty participants tested in our laboratory approximately 5 years prior. Participants were aged 97 (sd 09) years at baseline and 147 (sd 09) years at follow-up. Results Pre-puberty, boys consumed 68 (sd 48) servings/week and girls consumed 69 (sd 37) servings/week, while post-puberty boys consumed 115 (sd 53) servings/week and girls consumed 77 (sd 43) servings/week. Using Pearson correlation, SSB consumption was not significantly related to post-exercise airway narrowing at pre-puberty (r=-035, P=0130). In linear regression analyses, SSB consumption was significantly related to post-exercise airway narrowing post-puberty before (standardized =-060, P=0005) but not after (standardized =-033, P=0211) adjustment for confounders. Change in SSB consumption from pre- to post-puberty was significantly associated with post-exercise airway narrowing post-puberty (r=-061, P=0010) and change in post-exercise airway narrowing from pre- to post-puberty (r=-045, P=0048) when assessed via Pearson correlations. Conclusions These findings suggest a possible link between SSB consumption and asthma development during maturation. Reduced SSB intake may be a possible public health avenue for blunting rising asthma prevalence.
Citation: Emerson, S. R., Rosenkranz, S. K., Rosenkranz, R. R., Kurti, S. P., & Harms, C. A. (2016). The potential link between sugar-sweetened beverage consumption and post-exercise airway narrowing across puberty: a longitudinal cohort study. Public Health Nutrition, 19(13), 2435-2440. doi:10.1017/s1368980015003109
Keywords: Sexual Maturation; Bronchoconstriction; Soft Drinks; Diet; Asthma; Adolescence